Reliability and Validity of Attentional Style Questionnaire: Turkish Form - Yüksel, Müge; BELET, EDA ÖZTÜRK; Acar Bulut, Özlem; Nurlu, Merve; Çetintaş, Seyda (Hacettepe University, 2024)
Attention is an important part of cognitive and perceptual processes. Attention includes both external processes related to the environment and internal processes such as heredity. In addition, measuring attention processes, which have two dimensions, top-down and bottom-up, is important in terms of both learning processes and determining some psychopathologies. Based on this, it was aimed to adapt the Attention Style Questionnaire (ASQ) into Turkish in this study. The study group includes of 372 university students. Data collection materials included personal information form, Attention Styles Questionnaire and Control Dimension of Self-regulation Scale. Language validity and criterion-related validity analysis were performed for validity studies. Confirmatory factor analysis and test-retest analysis were utilized for reliability studies. The two-factor structure in the original structure of the scale was confirmed through confirmatory factor analysis results. Furthermore, the ASQ was found to be highly correlated with the Control Dimension of Self-regulation Scale. According to the findings obtained for reliability, Cronbach's alpha coefficients were found as .81 for the cognitive avoidance sub-dimension and .70 for the focusing sub-dimension. Test-retest correlation coefficients were determined as .76 for the cognitive avoidance sub-dimension and .75 for the focusing sub-dimension. Research results indicate that Attention Style Questionnaire is a reliable and valid measurement tool in determining the style of the attention to university students in Türkiye.
Keywords: Attention; Attention Style; Attention Control; CFA; Scale Adaptation